Developing and Promoting an Ecotourism Package Tour in the Mekong Delta at Vntour Joint Stock Travel Company - Tran, Thuy Tien (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Major in Digital Travel and Tourism Services Management